Effect of 6-hydroxydopamine on bovine adrenal chromaffin cells in culture. - Kirpekar, S. M. (Nature Publishing Group, 1983)
The effect of 6-hydroxydopamine on the catecholamine content and cell morphology of bovine adrenal chromaffin cells in culture was investigated. 6-Hydroxydopamine markedly reduced the catecholamine content of the cultured chromaffin cells after 6 and 24 h exposure. The effect was dose-related, with half-maximal depletion occurring at 2.4 X 10(-5) M. Cells exposed to 6-hydroxydopamine for 3 h and then to normal medium without the drug for 3 h more showed the same degree of toxicity as cells exposed to the drug for the entire 6 h. Ascorbate at high concentrations also exhibited toxicity toward chromaffin cells between 6 and 24 h of exposure. 6-Hydroxydopamine produced marked changes in cell morphology. At 1 h the cells appeared normal, at 3 h the processes were markedly shortened, and at 6 h they were completely retracted. On exposure for 24 h there were gross morphological changes and most cells were detached and free-floating in the medium. The toxicity of 6-hydroxydopamine in bovine adrenal chromaffin cells is discussed.